2011
DOI: 10.3109/00048674.2011.589368
|View full text |Cite
|
Sign up to set email alerts
|

13 Year Follow Up of Morbidity, Mortality and Use of Health Services Among Elderly Depressed Patients and General Elderly Populations

Abstract: An ICD-10 diagnosis of depressive disorder or dysthymia predicted increased use of psychiatric services, more psychiatric diagnoses and increased mortality, indicating poor late-life psychiatric outcome. Contrasting with other studies, depression did not predict increased use of somatic hospital services or more somatic diagnoses. The differences in health care status and use between elderly living in the capital and in rural areas elderly are novel findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Post-intervention effectiveness was well-documented, but follow-up periods of over one year were rare. Previous research suggests that depression is associated with faster physical decline and greater health service use (Djernes et al, 2011;Vaughan et al, 2015). Reducing depression may maintain physical functioning, rather than improve it, which may only be apparent in larger samples over longer follow up.…”
Section: Strengths and Limitations Of The Evidence Basementioning
confidence: 97%
See 1 more Smart Citation
“…Post-intervention effectiveness was well-documented, but follow-up periods of over one year were rare. Previous research suggests that depression is associated with faster physical decline and greater health service use (Djernes et al, 2011;Vaughan et al, 2015). Reducing depression may maintain physical functioning, rather than improve it, which may only be apparent in larger samples over longer follow up.…”
Section: Strengths and Limitations Of The Evidence Basementioning
confidence: 97%
“…difficulties carrying out activities of daily living due to physical health conditions, in addition to depression), have a four-fold increase in the risk of clinically significant anxiety or depression (Ni Mhaolain et al, 2012). Comorbid physical and mental health disorders increases the risk of greater frailty, mortality, and primary and secondary healthcare service use (Djernes et al, 2011;Vaughan et al, 2015). In an ageing population, demand for mental health services specific to later life is likely to increase.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of LLD is typically poor and is characterized by chronicity, mortality, and increased risk for cognitive impairment and progression to dementia. 6 We aim to evaluate the clinical effects of using a transcranial direct current stimulation (tDCS) protocol -a non-invasive therapeutic strategy in terms of safety and clinical impact -on depressive symptoms. The rationale for using tDCS for depression is based on its properties of increasing (anodal) and decreasing (cathodal) cortical excitability.…”
mentioning
confidence: 99%
“…For example, Unützer et al (2000) found that primary care patients older than 65 and suffering from depression experience much lower quality of life than non-depressed persons, and several studies (e.g. Brown et al 2011;Djernes et al 2011) have found that depressed older people had higher mortality rate. Also studies have shown that the prognosis for depression amongst older patients in primary care is poorer than amongst younger patients (e.g.…”
Section: Introductionmentioning
confidence: 99%